Large Medical Datasets on the Grid - de Alfonso, C.; Blanquer, I.; Hernández, V. (Methods of Information in Medicine, 2005)
Objective: This paper shows the use of the emerging Grid technology for gathering underused resources that are distributed among a corporate network. The work of these resources is coordinated for facing tasks which are not affordable by the individual usage of each of them.Methods: This paper shows an application for the projection, using Volume Rendering techniques, of huge medical volumes obtained from CTs and RMIs, adapted to Grid computing.Results: As a result the article shows the feasibility of the creation of an application based up on Grid technology, which solves problems that cannot be addressed by using common techniques. As an example, the article describes the projection of a huge medical dataset, which exceeds the resources of most common PCs, carried out by taking profit of idle CPU cycles from the computers of an organization.Conclusions: Grid technology is emerging as a new framework which allows gathering and coordinating resources distributed among a network (LAN or WAN), for addressing problems which cannot be solved through the single use of any of these resources. Medical Imaging is a clear application area for this technology.
Keywords: GRID; Medical Information computing; three-dimensional imaging